ASSEMBLY LINE BALANCING PROBLEMS WITH UNCERTAIN NUMERICAL PARAMETERS - Yu. N. Sotskov; A. S. Zatsiupa (Informatika)
Assembly line balancing problems with imprecise input data (durations of assembly operations, number of workstations) are considered. Problem settings with deterministic, stochastic, and uncertain parameters are discussed. Different approaches to the assembly line balancing problems with imprecise durations of assembly operations are analyzed. A new problem setting is proposed in which durations of assembly operations are given by lower and upper bounds of their possible values.